Efficacy and safety of Yaobitong capsule for acute lumbar disc herniation: A protocol for a multi-center randomized controlled trial. Issue 47 (25th November 2022) - Zhang, Xianshuai; Yang, Kexin; Wang, Siyi; Tang, Bin; Yin, He; Lei, Qunhui; Zhou, Guohui; Gu, Mingyu; Shi, Mingpeng; Zhao, Changwei; Li, Shaojun; Li, Zhenhua
Abstract : Background: There are few effective conservative therapies for acute lumbar disc herniation (LDH), and the choice of nonsteroidal anti-inflammatory drugs is not recommended for all patients. The purpose of this study was to compare the effect of Yaobitong capsule with celecoxib capsule, and to further confirm the safety and efficacy of Yaobitong capsule. Methods: This study is a large sample multicenter randomized controlled trial. Eight hospitals served as sub centers to recruit patients. A total of 258 patients are divided into Yaobitong group and celecoxib group according to the ratio of 1:1. Celecoxib or Yaobitong capsule was taken orally for 14 days. Patients will complete the trial after 3 months of follow-up, and independent statisticians who are blinded to random assignment will analyze the data using SAS 9.3 software. The primary outcome was the visual analogue scale (VAS) score after 14 days of treatment, and Japanese Orthopaedic Association (JOA), Oswestry Disability Index (ODI), and SF-12 will be regarded as secondary outcomes. Safety indexes will be recorded before and after treatment, and adverse events (AEs) will be recorded throughout this trial. Discussion: This study will evaluate the efficacy and safety of Yaobitong capsule in treating LDH. The experimental results will provide evidence support to treat LDH with Yaobitong capsule.